Ore-forming material sources of the Pb–Zn–(Ag–Fe–Cu) deposits in the northern Gangdese belt, Lhasa terrane: Constraints from geology, geochronology and S–Pb isotopes - Zhang, Aiping; Zheng, Yuanchuan; Fu, Qiang; Yang, Zhusen; Shen, Yang (Ore geology reviews, 2023)
[Display omitted] •The ore-forming biotite granite of the Longmala Pb–Zn–Fe–Cu deposit was emplaced at 54.6 ± 0.6 Ma.•The sulfur sources of the skarn Pb–Zn–(Ag), Pb–Zn–Fe–Cu and Fe–Cu deposits are mainly magmatic sulfur in the NGPB.•The ore-forming materials of Pb–Zn–(Ag) deposits originated from the S-type granites, whereas those of Pb–Zn–Fe–Cu and Fe–(Cu) deposits derived from the I-type granites. Many new skarn Pb–Zn–(Ag–Fe–Cu) deposits have been identified in the northern Gangdese polymetallic belt (NGPB). The NGPB comprises skarn deposits with different metal associations: Pb–Zn–(Ag), Pb–Zn–Fe–Cu, and Fe–Cu. The sources of ore-forming materials and whether intrusions contribute materials to these deposits, remain debated subjects. This study focused on zircon U–Pb dating and S–Pb isotopes of metal sulfides, ore-forming rocks, and wall rocks from the typical deposits in the three systems. Zircon U–Pb dating indicates that the biotite granite in the Longmala deposit was emplaced at 54.6 ± 0.6 Ma, which is consistent with its metallogenic age. The δ34S values of sulfides from the Pb–Zn–(Ag) deposits (Yaguila: −2.1‰ to + 6.0‰, Mengya’a: −0.8 ‰ to + 4.6 ‰) are similar to those from Pb–Zn–Fe–Cu deposits (Longmala: +1.6‰ to + 3.6‰, Lietinggang–Leqingla: −8.3 ‰ to + 2.0 ‰), suggesting a magmatic source of sulfur. The Pb isotopes of sulfides in Pb–Zn–(Ag) deposits (206Pb/204Pb = 18.4804–18.6935, 207Pb/204Pb = 15.6637–15.7331, and 208Pb/204Pb = 38. 0164–39.2612) are similar to those of the contemporaneous intrusions, as are those of Pb–Zn–Fe–Cu and Fe–Cu deposits, suggesting that the intrusions provided metals for the three systems. In comparison, the sulfides from the Pb–Zn–(Ag) deposits have higher 207Pb/204Pb values (15.6637 to 15.7331, mostly > 15.70) than the Fe–(Cu) deposits (15.6186 to 15.6848) and the Pb–Zn–Fe–Cu deposits (15.6163 to 15.7197), indicating that the metals of Pb–Zn–(Ag) deposits were derived from the upper-crust magma, whereas the metals of Fe–(Cu) and Pb–Zn–Fe–Cu deposits originated from the deep magma that required the involvement of mantle-derived components. Combined with previous research, we propose that the metals of Pb–Zn–(Ag) deposits originated from S-type granites, whereas those of Pb–Zn–Fe–Cu and Fe–(Cu) deposits were derived from I-type granites in the NGPB.